2013
DOI: 10.1097/ccm.0b013e318298291a
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Trial Comparing Physician Prompting With an Unprompted Automated Electronic Checklist to Reduce Empirical Antibiotic Utilization

Abstract: Objective To determine whether face-to-face prompting of critical care physicians reduces empirical antibiotic utilization compared to an unprompted electronic checklist embedded within the electronic health record (EHR). Design Random allocation design. Setting Medical intensive care unit (MICU) with high-intensity intensivist coverage at a tertiary care urban medical center. Patients Two hundred ninety-six critically ill patients treated with at least one day of empirical antibiotics. Interventions F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…Most evidence came from specialty settings (such as intensive care, emergency medicine and paediatrics); and from high‐risk patient groups (e.g. those at risk for or with infections); and from tertiary care …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most evidence came from specialty settings (such as intensive care, emergency medicine and paediatrics); and from high‐risk patient groups (e.g. those at risk for or with infections); and from tertiary care …”
Section: Resultsmentioning
confidence: 99%
“…In relation to practitioner performance, the studies reported improved turnaround time for first dose of antibiotic, improved selection of antibiotics (e.g. in line with local protocols), optimal dosing, improved adherence to guidelines/protocols, and a decrease in the total number of antibiotics prescribed . Some studies also reported a reduction in prescribing errors and increased de‐escalation, as well as improved antibiotic sensitivity and increase in sensitivity of surgical site infection detection .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, proper culturing procedures foster patients’ receipt of indicated targeted therapy; the prompt switch from IV to PO may result in shorter inpatient stays 11 ; accurate drug allergy histories promote optimal therapy 12 ; and antibiotic timeouts have been shown to decrease empiric antibiotic therapy. 13 We were interested in 1) participants’ attitudes regarding the belief that nurses should play a major role in antibiotic stewardship; 2) challenges to nurses’ ability to perform recommended practices; and 3) ways to address identified challenges. We also spoke with IPs, all of whom were trained nurses and held nursing education responsibilities, since they would likely offer a unique perspective on this topic.…”
mentioning
confidence: 99%
“…Reminder systems and stickers have previously been successfully implemented and have changed healthcare in a variety of areas, such as: reducing immunisation drop out rates, improving use of thromboprophylaxis to prevent deep venous thrombosis and improving documentation of resuscitation status; however, the sustainability of these systems has not been fully established. A compulsory computerised system incorporated into an electronic prescribing system or medical record could potentially improve uptake of a reminder system; however, it is likely that it is the discussion around the use of antimicrobials and the subsequent learning that encourages a sustained change in behaviour . We believe that future research in this area needs also to address the social complexities in the process of appropriate antimicrobial prescribing to find sustainable strategies that also fit clinical workflow for busy staff …”
Section: Discussionmentioning
confidence: 99%
“…A compulsory computerised system incorporated into an electronic prescribing system or medical record could potentially improve uptake of a reminder system; however, it is likely that it is the discussion around the use of antimicrobials and the subsequent learning that encourages a sustained change in behaviour. 32,33 We believe that future research in this area needs also to address the social complexities in the process of appropriate antimicrobial prescribing to find sustainable strategies that also fit clinical workflow for busy staff. 34 There are multiple explanations for inappropriate prescribing in a busy hospital ward.…”
Section: Discussionmentioning
confidence: 99%